Hardness Optimization of Heat Treatment Process of Bucket Teeth Excavator - Suryo, Sumar Hadi; Adi Widyanto, Susilo; Paryanto, Paryanto; Mansuri, Aly Syariati (Salehan Institute of Higher Education, 2018)
Excavator is heavy equipment that usually used in construction and mining works. Bucket teeth which are located in the tip of bucket excavator are used for digging works. They are easily damaged by direct contact with the media. One of the material used in bucket teeth excavator is mild carbon steel that has carbon content between 0.33%-0.5%. However, the hardness value of this material is not yet meets the standard of bucket teeth excavator so the optimum hardness value based on its heat treatment should be known. Besides that, its tensile, impact strength, and micro structure in optimum condition will also know. Optimization method was done through Taguchi experimental design with L9 orthogonal and ANOVA (Analysis of Variance). Factors or parameters in this research were heating temperature, holding time, quenching media, and tempering temperature. In this experiment, nine specimens of mild carbon steel were tested by different heating temperatures (850oC, 875oC, 900oC), different holding times (60, 90, and 120 minutes), different quenching medias (oil, water, and salt water), and different tempering temperatures (250oC, 450oC, 650oC). Calculation of Taguchi method and confirmation experiment showed that the optimum parameters of hardness are 875oC heating temperature, 60 minutes holding time, water quenching media, and 250oC tempering temperature. Meanwhile, ANOVA test showed a result that the four factors had an effect on the bucket teeth excavator hardness.